Upaya Mengasah Kecerdasan Linguistik dan Interpersonal melalui Program Trainer Muda - Maftuchaturrohmah Maftuchaturrohmah; Asriana Kibtiyah (LP2M STIT Palapa Nusantara, 2022)
The general public's view of the meaning of intelligence is still narrow. Many think that intelligent children are children who have logical intelligence and those who are lacking in that are considered unintelligent, even though there are many other types of intelligence. Some of these intelligences are linguistic and interpersonal intelligence. One way to hone linguistic and interpersonal intelligence is through a youth trainer program. The purpose of this research is to find out about the youth trainer program, how to hone linguistic and interpersonal intelligence through the youth trainer program, and what are the supporting and inhibiting factors. This research is a qualitative research using a case study approach. Data collection techniques using observation, interviews, and documentation. In the interview process, the researchers obtained data from the training division, teachers, administrators and students. Data analysis technique by reducing data, presenting data and drawing conclusions. The technique of checking the validity of the data by extending participation and triangulation. The conclusion of the research is that through the young trainer program, the students' linguistic and interpersonal intelligence has been proven to be honed. The supporting factors in this research are: imagination map, peer tutoring, teaching flash students etc. The inhibiting factor: training activities sometimes clash with the formal school schedule, the varying abilities of students and the lack of self-motivation of some students.